Rapid Assessment of Trachoma in Underserved Population of Car-Nicobar Island, India - Vashist, Praveen (Public Library of Science, 2013)
PURPOSE: To determine the burden of trachoma and its related risk factors amongst the native population of Car-Nicobar Island in India. METHODS: Rapid assessment for trachoma was conducted in ten villages of Car- Nicobar Island according to standard WHO guidelines. An average of 50 children aged 1–9 years were assessed clinically for signs of active trachoma and facial cleanliness in each village. Additionally, all adults above 15 years of age in these households were examined for evidence of trachomatous trichiasis and corneal opacity. Environmental risk factors contributing to trachoma like limited access to potable water & functional latrine, presence of animal pen and garbage within the Nicobari hut were also noted in all villages. RESULTS: Out of a total of fifteen villages in Car-Nicobar Island, ten villages were selected for trachoma survey depending on evidence of socio-developmental indicators like poverty and decreased access to water, sanitation and healthcare facilities. The total population of the selected clusters was 7277 in the ten villages. Overall, 251 of 516 children (48.6%;CI: 46.5–55.1) had evidence of follicular stage of trachoma and 11 children (2.1%;CI:1.0–3.4) had evidence of inflammatory stage of trachoma. Nearly 15%(CI:12.1–18.3) children were noted to have unclean faces in the ten villages. Trachomatous trichiasis was noted in 73 adults (1.0%;CI:0.8–1.2). The environmental sanitation was not found to be satisfactory in the surveyed villages mainly due to the co-habitance of Nicobari people with domestic animals like pigs, hens, goats, dogs, cats etc in most (96.4%) of the households. CONCLUSION: Active trachoma and trachomatous trichiasis was observed in all the ten villages surveyed, wherein trachoma control measures are needed.